Cooperative Donor–Acceptor Interactions in Stabilizing Carbene‐Borane and Carbene‐Alane Compounds: A Theoretical Insight. Issue 7 (16th February 2020) - Dutta, Sayan; De, Sriman; Bose, Sanjoy; Mahal, Eti; Koley, Debasis
Abstract : Density functional theory calculations have been performed to elucidate the electronic structure and bonding scenario in various carbene‐borane (L BX₃ ) and carbene‐alane (L AlX₃ ) compounds (X = ‐H, ‐Me, ‐Cl, ‐Ph, ‐C6 F5 ). We have performed extended transition state (ETS) analysis to reveal the nature of the donor–acceptor bonds ( C c arb –E; E = B, Al) and also for the assessment of the intrinsic donor–acceptor strength in this class of compounds. Our computations suggest that the C c arb –Al bonds in all the L AlX₃ adducts have substantially higher electrostatic nature than covalent character. Conversely, the nature of the C c arb –B bonds in L BX₃ have a strong dependence on the electronic nature of both carbene and borane. Moreover, unlike alanes in L AlX₃, the intrinsic Lewis acid strength of the boranes in L BX₃ has a strong dependence on the electronic nature of the carbenes. We have also explored the correlation of the interaction energies (Δ E int ) with various bonding parameters i.e., geometrical and Natural bond orbital (NBO) parameters of L EH₃ . Furthermore, natural orbital for chemical valence (NOCV) calculations are performed to have a qualitative understanding of the relative σ‐donating and π‐accepting abilities of the carbenes in L EH₃ . Additionally, we have investigated the abilities of carbenes to activate the B–H bonds in BH3 and pinacolborane. ETS analysis shows a strong dependence of the B–H activation barriers on the distortion energies of both carbene and borane fragments. Abstract : Detailed computational investigations of the electronic structure and bonding scenarios in various carbene‐borane and carbene‐alane compounds are presented. We performed ETS analysis for the assessment of the intrinsic donor–acceptor strength and NOCV calculations to reveal the relative σ‐donating and π‐accepting abilities of the carbenes. Their abilities to activate the B–H bonds in BH3 and pinacolborane were also studied.